Quant: a rocket scientist - Zambrano Norabuena, Jorge Luis (2022)
Although we know that graduates of the Systems Engineering Career of the University of Lima, throughout their academic training, they have developed a series of skills that allow them to suggest, lead, verify and manage a series of improvements and / or innovative solutions supported by the use of information technologies (IT), satisfying the needs of the organization to which it belongs. As an organization becomes increasingly complex, the demand for these new professionals of the specialty, who, in addition to having the ability to understand complex mathematical models, can also continue to generate profits and at the same time, measure and control the risk inherent to said operations. On this particular trip, said professional development began within one of the main financial entities in Peru and through various teams and units traditionally little or nothing related to Systems or IT. Likewise, although we can believe that only in the banking and / or financial world can these professionals be developed, we will see how even in the corporate world and, with greater incidence in the real sector, this profile still has a lot to contribute and generate due value to the low incidence of technology and mathematical concepts used there. Finally, through this document it is intended to tell the professional trajectory of a graduate of the faculty of systems engineering, who, applying the concepts and tools transmitted during the university stage, can develop innovative solutions in solving problems common to finance, modeling in this way a different profile experience called financial engineer or quant.